Analysis of Accounting Treatment for Zakat, Infaq, and Sadaqah Considering on PSAK Number 109 at Zakat Management Organizations - Nur, Nashri; Alam, Syamsu; Junaid, Asriani (Manunggal Halim Jaya, 2025)
This study aims to determine the conformity of the accounting treatment for Zakat, Infaq, and Sadaqah at BAZNAS South Sulawesi as reviewed under PSAK Number 109. The research employs a descriptive analytical approach, involving direct investigation of the research subject, and collecting and analyzing documents or records maintained by the organization regarding their accounting and financial reporting. The methodology includes interviews with key personnel, review of financial statements, and comparative analysis with PSAK Number 109 standards. The urgency of this research lies in the need to enhance transparency and accountability in the management of charitable funds, ensuring compliance with regulatory standards, and improving public trust in Zakat management. The results indicate that the recognition and measurement of Zakat, Infaq, and Sadaqah at BAZNAS South Sulawesi are consistent with PSAK Number 109, except that the presentation and disclosure of financial reports are not fully compliant with PSAK Number 109.